2008
DOI: 10.1111/j.1537-2995.2008.01651.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet count is a sensitive predictor of autologous peripheral blood progenitor cell collection yield in previously treated plasma cell disease patients

Abstract: BACKGROUND-It is often a clinical dilemma to determine when to collect autologous peripheral blood progenitor cells (PBPCs) in patients who received prior chemotherapy. It is also challenging to predict if the collected cells will be enough for one or two transplants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 28 publications
(30 reference statements)
2
23
1
2
Order By: Relevance
“…We also observed in this study that mobilization capacity affected time to platelet engraftment but not time to neutrophil engraftment. Our previous report shows time to platelet engraftment is more responsive to HSC dose than time to neutrophil engraftment 26 . This finding explains the observation that time to platelet engraftment was statistically significantly shorter in high mobilizers.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We also observed in this study that mobilization capacity affected time to platelet engraftment but not time to neutrophil engraftment. Our previous report shows time to platelet engraftment is more responsive to HSC dose than time to neutrophil engraftment 26 . This finding explains the observation that time to platelet engraftment was statistically significantly shorter in high mobilizers.…”
Section: Discussionmentioning
confidence: 92%
“…23 The quality of collected HPC is defined by proportion of primitive HSC subsets (CD34+CD38−, CD34+HLA-DR−, and CD34+ in G0 stage of cell cycle) 24 , the proportion of HSCs that express CXCR4 and CD26 homing proteins 8,25 , and days to neutrophil and platelet engraftments post transplant. 26 However, the correlation of the quantity and the quality of the HSCs in the autologous BMT setting is unclear. In this study, we tested the hypothesis that HSCs collected from low mobilizers are qualitatively inferior to HSCs from high mobilizers.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a lot of investigations of predictive factors that could influence mobilization and collection of PBSC in order to improve efficacy and safety of mobilization and harvestration [19][20][21][22][23][24][25][26][27]. There are still a lot of contradictory in the different studies that work on this issue and final conclusions cannot be made, primarily because of heterogeneity of the donors.…”
Section: Discussionmentioning
confidence: 91%
“…Zubair et al showed that platelet count before growth factor administration significantly correlated with the total CD34+ cell yield (Spearman r = 0.38, p < 0.001). With a multiple linear regression model (adjusted R2 = 0.31, AIC = 63.1), it has been determined that the baseline platelet count significantly correlated with total CD34+ cell yield in treated plasma cell disorder patients in their study [19]. Although there was no significant association between CD34+ cell × 10 6 /kg and blood parameters in the study of Garicoa et al, they found out that leukocyte count higher than 30 × 10 9 /L and monocyte count higher than 1.8 × 10 9 /L could be predictive factors of efficient collection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation